Is AI in Healthcare Ethical? Navigating the Moral Imperatives of Digital Medicine - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Is AI in Healthcare Ethical? Navigating the Moral Imperatives of Digital Medicine The integration of Artificial Intelligence (AI) into healthcare is rap...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care